Corruption in the private sector and the role of the public in its prevention - Білецький, Андрій Володимирович (Problems of legality, 2016)
The article analyzes the phenomenon of corruption in the private sector. The author defined basic legislative acts which contain the concept of corruption in the private sphere. It should be noted that the compliance is the primary tool to combat corruption in the private sector. There were also explored basic shapes of corruption in the private sector. The author suggests that the public and business should cooperate in following areas to prevent corruption in the private sector: formation and implementation of the anti-corruption policy of a company; formation of the anti-corruption culture, monitoring and detection of the information, execution of the control, intermediary activity between business and government.